Konsep Himpunan dalam Matematika Diskrit - Olivia Lisna Wati; Nayla Desviona; Novi Permasari; M. David Alfikri; Raja Abdul Rahman Shah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
Set theory is one of the fundamental concepts underlying the structure of discrete mathematics and computer science and plays a crucial role in understanding various advanced topics, such as relations, functions, mathematical logic, and other discrete structures. This concept serves as the foundation for developing a systematic and structured mathematical mindset. This paper aims to explain the fundamental concepts of set theory, review its significance in discrete mathematics, and outline how to present sets and basic operations on sets, such as union, intersection, complement, and difference. The method used in this paper is a literature study by reviewing, collecting, reading, and analyzing data from various relevant written sources, both textbooks and scientific articles. Through this study, students are expected to be able to understand set theory more comprehensively. Thus, it can be concluded that set theory is not merely an introductory topic, but rather a formal framework that defines the validity of logic and structure in modern discrete systems.